Praperadilan Terhadap Penghentian Penyelidikan Kasus Pelanggaran HAM Berdasarkan Rekomendasi Komnas HAM - Rijal , Syamsul; Nawi, Syahruddin; Salle, Salle (Innovative: Journal Of Social Science Research, 2025)
Abstract The study adopted the sounatit approach through research of the ideal prancadilan concept of the destruction, investigation, already obtained of human rights abuses. Research shows that, according to a law enforcement initiative, pretrial measures for the termination of the investigation of the suspected human rights abuses that have obtained the recommendation of the komnas ham asa horizontal surveillance mechanism for testing the actions of law enforcement officials asa safeguard against arbitrary action of law enforcement officials, as well asa recommended statement made by human rights officials is illegal, as well as non-binding, non-binding, non-performing, The referrals suggest that human rights abuses in Indonesia are not exempt from book m. The study recommends that governments and congress submit termination, the human rights inquiry enters as a pretrial object, in the design, under a new program of law (kuhap) and a change of weight. Section no.39: jabun 1999 on human rights to provide employment, bea Keywords: pretrial, termination of inquiry, recommendation